Be10 and U-series isotopes in manganese from the Central North Pacific - Teh-Lung Ku; Akiko Omura; P S Chen (PANGAEA, 1972)
The exponential decreases with depth of 10Be , 230Th and 231Pa in two manganese nodules from the central North Pacific is interpreted in terms of slow growth of the nodules: at average rates of millimeters per million years. It is observed in one specimen (Mn 139): 10Be-based rate 230Th-based rate < 231Pa-based rate. This suggests that diffusion-mixing may have modified the depth gradients of these nuclides, such that the true rate would be close to or even lower than the observed 10Be rate of 1.3 mm/10-6 yr. Quantitative assessment using a diffusion-decay model indicates that in Mn 139, 230Th and 231Pa could have been subjected to diffusion-like transport with an effective diffusion coefficient of about 1 10power8xcm-2/yr. After correction for this effect, the 230Th and 231Pa data give a concordant rate of 1.9 mm/10-6 yr, about 2-3 times lower than their uncorrected values. The small and variable amounts of integrated dpm/cmSUP-2 of 10Be, 230Th excess and 231Pa excess found in nodules are best explained by their incorporating only a fraction of the nuclides supplied due to frequent coverage of sediments. The alternative explanation of young extquotesingleexposure extquotesingle ages is refutable on several grounds. Among these, it is shown that diffusion of nuclides required by the exposure-age concept yields depth profiles that are not of the commonly observed exponential form.
Supplement to: Ku, T-L et al. (1979): Be10 and U-series isotopes in manganese from the Central North Pacific. In: Bischoff, J.L., Piper, D.Z. (Eds.), Marine Geology and Oceanography of the Pacific Manganese Nodule Province. Marine Science, Plenum Publishing Corporation, New York, U.S.A., 791-814, https://doi.org/10.1007/978-1-4684-3518-4_26